2022
DOI: 10.1111/dar.13455
|View full text |Cite
|
Sign up to set email alerts
|

A rural ecosystem of recovery: Lessons from substance users' experiences of accessing services in Western Australia's South West

Abstract: Introduction Substance use is a public health issue with a greater burden in rural areas. Barriers to accessing services are exacerbated for rural substance users, with confidentiality concerns, longer travel distances, workforce issues and limited availability of services. This paper presents results from a study exploring substance users' experiences of accessing services in Western Australia's South West. Methods This qualitative study was informed by phenomenology, and drew from social determinants and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The Orange Declaration calls for new service models tailored to context and better-aligned funding models that reward collaboration (9). Our experience and recent research on AOD and mental health services provide evidence that the current commissioning models are not aligned with the Orange Declaration, and remain largely metro-centric and reliant on a narrow conceptualization of service accessibility that does not take into account the heterogeneity of the rural experience (18,19).…”
Section: Context-based Accessibility: the Orange Declarationmentioning
confidence: 93%
See 1 more Smart Citation
“…The Orange Declaration calls for new service models tailored to context and better-aligned funding models that reward collaboration (9). Our experience and recent research on AOD and mental health services provide evidence that the current commissioning models are not aligned with the Orange Declaration, and remain largely metro-centric and reliant on a narrow conceptualization of service accessibility that does not take into account the heterogeneity of the rural experience (18,19).…”
Section: Context-based Accessibility: the Orange Declarationmentioning
confidence: 93%
“…In our recent research on substance users' experiences of accessing AOD services in WA's South West region, we applied a socio-ecological lens and identified service gaps and limited intra-and inter-sectoral collaboration, most notably between community-based state-funded services and primary healthcare providers and between the AOD and the mental health services sectors (18). We also found that existing local services were able to effectively respond to a crisis such as the COVID-19 pandemic by assertively and flexibly adapting their service provision to suit local needs, against urban-centric commissioning parameters (19).…”
Section: Context-based Accessibility: the Orange Declarationmentioning
confidence: 99%